Leadless left ventricular endocardial pacing for CRT upgrades in previously failed and high-risk patients in comparison with coronary sinus CRT upgrades. Issue 10 (28th July 2021) - Sidhu, Baldeep Singh; Sieniewicz, Benjamin; Gould, Justin; Elliott, Mark K; Mehta, Vishal S; Betts, Timothy R; James, Simon; Turley, Andrew J; Butter, Christian; Seifert, Martin; Boersma, Lucas V A; Riahi, Sam; et al.
Abstract: Aims: Cardiac resynchronization therapy (CRT) upgrades may be less likely to improve following intervention. Leadless left ventricular (LV) endocardial pacing has been used for patients with previously failed CRT or high-risk upgrades. We compared procedural and long-term outcomes in patients undergoing coronary sinus (CS) CRT upgrades with high-risk and previously failed CRT upgrades undergoing LV endocardial upgrades. Method and results: Prospective consecutive CS upgrades between 2015 and 2019 were compared with those undergoing WiSE-CRT implantation. Cardiac resynchronization therapy response at 6 months was defined as improvement in clinical composite score (CCS) and a reduction in LV end-systolic volume (LVESV) ≥15%. A total of 225 patients were analysed; 121 CS and 104 endocardial upgrades. Patients receiving WiSE-CRT tended to have more comorbidities and were more likely to have previous cardiac surgery (30.9% vs. 16.5%; P = 0.012), hypertension (59.2% vs. 34.7%; P < 0.001), chronic obstructive airways disease (19.4% vs. 9.9%; P = 0.046), and chronic kidney disease (46.4% vs. 21.5%; P < 0.01) but similar LV ejection fraction (30.0 ± 8.3% vs. 29.5 ± 8.6%; P = 0.678). WiSE-CRT upgrades were successful in 97.1% with procedure-related mortality in 1.9%. Coronary sinus upgrades were successful in 97.5% of cases with a 2.5% rate of CS dissection and 5.6% lead malfunction/displacement. At 6 months, 91 WiSE-CRT upgrades and 107 CS upgrades had similar improvements in CCS (76.3% vs. 68.5%; P = 0.210) and reduction in LVESV ≥15% (54.2% vs. 56.3%; P = 0.835). Conclusion: Despite prior failed upgrades and high-risk patients with more comorbidities, WiSE-CRT upgrades had high rates of procedural success and similar improvements in CCS and LV remodelling with CS upgrades. Graphical Abstract: